Dinamika Interaksi Publik pada Isu Sosial Viral di Media Sosial: Studi Wacana di Instagram dan X - hasmuni; Safrizal (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This study aims to analyze public interaction patterns within the dynamics of opinion wars on viral social issues in 2025, using Instagram and X (Twitter) as case studies. Viral phenomena are understood as arenas of meaning production and exchange, where users respond through comments, reposts, and hashtag participation. This research employs a qualitative method with a discourse analysis approach to explore message construction, interaction patterns, and public opinion orientation. Symbolic Interaction Theory is used to explain how meanings are created and negotiated among users, while the Spiral of Silence Theory is applied to understand the tendency of users to support or withhold opinions based on the dominance of the majority opinion in digital spaces. Data were collected through the documentation of 250 viral posts on Instagram and X, as well as an analysis of over 10,000 comments and 1,500 retweets between January and April 2025, during the peak period of viral issue visibility. The findings indicate that opinion wars are driven not only by ideological differences but also by algorithmic mechanisms that amplify the visibility of specific messages. Public interactions tend to form two dominant camps that reinforce their narratives through comments, retweets, and symbolic support. It was also found that users with minority opinions are more likely to remain silent or migrate to closed discussion spaces, such as WhatsApp groups or Instagram’s Close Friends feature. This study concludes that opinion wars on social media are communicative processes influenced by symbolic meaning, social pressure, and algorithmic amplification, which may exacerbate social polarization. The findings provide deeper insights into the dynamics of public opinion formation and the impact of algorithms on digital communication in the 2025 social media environment.